Complete Release of Superficial Medial Collateral Ligament in TKA: Surgical technique and mid-term results - Prateeptongkum, MD, Pongporn; Tanavalee, MD, Aree; Mekrungcharas, MD, Natdhadej; Ngarmukos, MD, Srihatach (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Intraoperative medial collateral ligament (MCL) injury or attenuation during total knee arthroplasty (TKA) has been reported with satisfactory clinical knee function and stability. However, there was no report on clinical outcomes and knee stability following intentionally complete release of intact superficial MCL (sMCL) during TKA. We demonstrated the surgical technique of sMCL release and reported mid-term clinical outcomes. Methods: A consecutive series of 35 patients, who underwent TKA and had intraoperatively complete release of sMCL using the subperiosteal technique previously described by Insall, was evaluated for clinical outcomes and knee stability. The surgical technique for sMCL release, the prosthesis and the postoperative rehabilitation protocols were uniform without additional external knee support. A digital dynamometer was used for the quantitative measurement of knee stability in the mediolateral plane at a static 20-lb force. Laxity of the MCL was graded as 0, 1+ and 2+ if the gap was 0 mm, > 0 mm and ≤ 5 mm, and > 5 mm, respectively. Weight-bearing radiographs of patients at the latest follow up (FU) were evaluated. Results: Preoperatively, the mean tibiofemoral varus angle of the studied group was 14.3° (±6.4°). The mean age and body mass index (BMI) were 70 years, 26.4 kg/m2, respectively. The 10- to 12-mm polyethylene inserts were used in 5% of patients, whilst 14- to 17-mm inserts were used in 95% of patients. At the mean 6-year FU (range: 2-8 years), the mean Knee Society (KS) clinical and function scores were 94.3 and 84.2 points, respectively. The mean maximum range of motion (ROM) was 135.1°. Regarding the knee stability test, knees with grade 0, 1+ and 2+ were found in 84.4%, 15.6% and 0%, respectively. One patient in the studied group had revision due to infection. The 6-year survivorship for reoperation related to MCL instability was 100%. Conclusion: During ligament balancing for varus knees in TKA, some surgeons tend to avoid performing complete release of the sMCL due to concerns on postoperative knee instability. The subperiosteal release of the sMCL made a full-thickness layer of medial soft tissue attaching with the sMCL, which provided adequate strength to withstand the valgus stress force from daily function. According to the present study, it confirmed a satisfactory mid-term result of TKA with subperiosteally complete release of sMCL in terms of clinical outcomes, knee stability, range of motion, and survivorship. However, it was found that a thicker polyethylene insert related to the release was more common. In conclusion, subperiosteally complete release of the sMCL during TKA provided reliable postoperative medial soft tissue tension and clinical results at mid-term.